105-3x=33x+17

Simple and best practice solution for 105-3x=33x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 105-3x=33x+17 equation:


Simplifying
105 + -3x = 33x + 17

Reorder the terms:
105 + -3x = 17 + 33x

Solving
105 + -3x = 17 + 33x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-33x' to each side of the equation.
105 + -3x + -33x = 17 + 33x + -33x

Combine like terms: -3x + -33x = -36x
105 + -36x = 17 + 33x + -33x

Combine like terms: 33x + -33x = 0
105 + -36x = 17 + 0
105 + -36x = 17

Add '-105' to each side of the equation.
105 + -105 + -36x = 17 + -105

Combine like terms: 105 + -105 = 0
0 + -36x = 17 + -105
-36x = 17 + -105

Combine like terms: 17 + -105 = -88
-36x = -88

Divide each side by '-36'.
x = 2.444444444

Simplifying
x = 2.444444444

See similar equations:

| 7-10x=20-17x | | 2x+31=9x-32 | | 3x+7=-113-9x | | 12x-3=10+5 | | 141-6x=4x+11 | | 2x+12x-14-12=24x+30 | | 137-6x=6x+5 | | 5x+24=13x-72 | | 5y-20=(3x*4)+5 | | 5x+5=85-5 | | n-12=17 | | 2t+-7-5t=11 | | -(5y+5)-(-4y-8)=0 | | 650-5p-p^2=0 | | 6(x-2)=9x-3(2x-1) | | 3-x=15 | | 5x+22=13x-58 | | x=x-x*x | | 6x+22=13x-48 | | n+38=52 | | 5x^2+x-.25=0 | | 0.80+.05(18-x)=.10(-66) | | X^2+17+42=0 | | 3x+5=4-5x | | -24c=36c | | 5x^2-16x+15x=4x-5 | | 1x+6x-7-6=12x+15 | | 2(3-x)=5(4x-1) | | 8x-2=11x+7 | | .5(5x+4)-.33(x+7)=4 | | 81+8=6+5 | | 3x+15=33 |

Equations solver categories